Clinical Characteristics of Ulcerative Colitis in Nepalese Population: Experience from a Tertiary Care Center TUTH, Kathmandu, Nepal (Journal of Nobel Medical College, 2015)
Background and Aim: Rising incidence and prevalence of ulcerative colitis (UC) had been observed in Asian countries. We conducted a study in our center, aiming to describe the demographic and clinical characteristics of UC in Nepalese population.Method: This is a cross sectional study of patients with diagnosis of UC in our hospital from Feb 2014 to Jan 2015. The diagnosis of UC has to satisfy the internationally accepted criteria. All patients were Nepalese and Clinical and epidemiological data were obtained and analysed through SPSS version 20.Results: 60 patients were included in the study. Mean age at diagnosis was 34.6 years. Male had slight preponderance with M:F (1.06:1). Mean duration of disease at diagnosis was 3.7 years. 83% had rectal bleed, Diarrhoea was seen in 77.3%, Tenesmus and Urgency in 70%, Mucus in stool was found in 65%, abdominal pain in 55%. 16.7% had weight loss and extraintestinal manifestations whereas fever was seen in 8.3%. In our patients 38.3% had ulcerative proctitis and 50% had left-sided UC, whereas 11.7% had extensive UC at presentation. The majority presented with mild (53.3%) or moderate (38.3%) disease activity, only 8.3% with severe disease.Conclusions: The peak age of UC was similar to other Western and Asian countries but second peak reported in western countries have not been seen in this study. This finding is similar to reports from East Asia. Similarly the proportion of patients with extra intestinal manifestations was low in our study as compared to studies reported from western world. Our study also showed that it takes longer to diagnose UC in Nepal. This might be related to the unawareness of the patients’ and lack of availability of the diagnostic resources.Journal of Nobel College of Medicine Vol.4(1) 2015: 1-5